Increase Cotton Yield Based on the Application of Laser Radiation in Agriculture - To’rayev Ergash Yuldashevich; Xalilova Mohidil Davlatovna (Researchparks Publishing, 2021)
Experiments were used to investigate the positive impacts of external influences on the development and production of rural horticulture crops, including radiation, temperature, pressure, electric, and magnetic fields, as well as the qualities of the effects that give positive outcomes.